Clinical frailty scale as a predictor of outcome in elderly patients affected by moderate or severe traumatic brain injury - Zacchetti, Lucia; Longhi, Luca; Zangari, Rosalia; Aresi, Silvia; Marchesi, Federica; Gritti, Paolo; Biroli, Francesco; Lorini, Luca Ferdinando (Frontiers in Neurology, 2023)
Background Older age is a well-known risk factor for unfavorable outcome in traumatic brain injury (TBI). However, many older people with TBI respond well to aggressive treatments, suggesting that chronological age and TBI severity alone may be inadequate prognostic markers. Frailty is an age-related homeostatic imbalance of loss of physiologic and cognitive reserve resulting in both limitation in autonomy of activities of daily living and vulnerability to adverse events. We hypothesized that frailty would be associated with 6-month adverse functional outcome in older people affected by moderate or severe TBI. Methods This was a single-center prospective observational study. We enrolled consecutive patients aged ≥65 years after TBI with Glasgow Coma Scale ≤13 and admitted to our Neurosurgical Intensive Care Unit. Frailty was evaluated by Clinical Frailty Scale (CFS). Relationships between TBI severity, frailty and extended Glasgow Outcome Scale (GOSE) at 6-month were evaluated. Results Sixty patients were studied, 65% were males, their age was 76 years (IQR 70–80) and their admission GCS was 8 (IQR 6–11) with a GCS motor score of 5 (IQR 4–5). Twenty eight were vulnerable-frail (defined as CFS ≥ 4). Vulnerable-frail patients showed greater 6-month mortality and unfavorable outcome compared to non-frail [87% vs. 30% OR and 95% CI: 15.7 (3.9–55.2), p < 0.0001 and 92% vs. 51% OR and 95% CI: 9.9 (2.1–46.3), p = 0.002]. In univariate analysis patients with unfavorable outcome were more frequently male and vulnerable-frail, had a higher prevalence of pre-existing neurodegenerative disease, abnormal pupil, lower GCS and had worst CT scan characteristics. At multivariate analysis, only CFS ≥ 4 and traumatic subarachnoid hemorrhage remained associated to 6-month outcome. Conclusion Frailty was associated with 6 month-outcome, suggesting that the pre-injury functional status could represent an additional indicator to stratify patient’s severity and to predict outcome.